KAJIAN KEPUASAN TERHADAP WEBSITE UNIVERSITAS AIRLANGGA: Studi Komparasi antara Pengguna Internal dan Pengguna Eksternal/Potensial - , Dewi Puspitasari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Good website is a that much in demand by users. For those reasons, this study is important because you want to examine the quality of website according to the user's view of Airlangga University students and prospective student users. This research used WebQual 4.0 by using the dimensions of usability, information quality, and interaction quality and was conducted from March 2013 to June 2013, with a total sample of 100 students of Airlangga University and 100 high school students in Surabaya. After analyzing the questionnaires from a sample of students and prospective students can be concluded that the usefulness and quality of information significantly affects user satisfaction Airlangga University website. While the quality of the interaction does not significantly affect the user satisfaction Airlangga University Directorate website. Next is the opinion relates to the comparison between the sample and the sample of students prospective students regarding University Press website. The results showed that the usability of Airlangga University website seen by prospective students is higher than the student. Similarly, the quality of information and interaction quality website by Airlangga University prospective student ratings of greater value than the Airlangga University student assessment. So that it affects the level of satisfaction of users of a group of prospective students is also higher than the valuation of Airlangga University student group.